SURAKARTA Comic Art Center - Chandra, Nicko; , Suryaning Setyowati, ST. MT (2016)
The comic book is a book of fiction and non-fiction in presentation with images accompanied by text. Comic books have many kinds, in terms of form in terms of content to the story presented. Comic books can be enjoyed by the community from an early age until adulthood. The main function of the comic is as a means of entertainment and leisure time fillers. In addition to these two functions the comics, comics can be a means of studying the equivalent of kindergarten to Graduate. The general public more quickly comprehend the book presenting the image of a book on the present text. Indonesia is the second country to become the world's largest comic book connoisseur after the country Japan. In addition in the form of books, comic books have a variety of end products. The product can be a comic book other works such as movies, cartoons, action figures, merchendise. The United State and Japan are the countries that made the comic book as a culture. Comic books can give you a great influence to the society in a country. Indonesia is one of the countries that have a history of the development of the comic books. In the period 1970 - 1990 was a golden period of development, UN comic book Indonesia. Comic book titled "Gundala Putra Petir, Godam, Pandji Tengkorak" is an original comic book Indonesia. Comic progress along with advanced technology. The development of comic books can be seen in terms of story and in terms of image quality. Surakarta is one city that has a history of comic books. 88.7% community Surakarta liked comic books. Comic book connoisseur in Surakarta is not in balance with the existing facilities. Listed there are 6 facilities that sell comic books and 2 facilities that rent out comic books. 70.6% of community facilities that are not aware of Surakarta provides comic books. Community city of Surakarta has the famous cartoonists, namely Chris Lie and Numbo Afif. They are the comic origin of Surakarta to become national comics up to international.